Prehospital emergency medical service utilization and associated factors among critically ill COVID-19 patients treated at centers in Addis Ababa, Ethiopia. - Ararso Baru Olani; Lemlem Beza; Menbeu Sultan; Tariku Bekelcho; Michael Alemayehu (Public Library of Science (PLoS), 2023)
The majority of populations in developing countries are living in areas of no access or limited access to prehospital emergency medical services (EMS). In Addis Ababa, the reported prehospital EMS utilization were ranging from zero to thirty-eight percent. However, there is limited research on reasons for the low utilization of prehospital resources in Ethiopia. This study aimed to assess factors associated with prehospital EMS utilization among critically ill COVID-19 patients in Addis Ababa, Ethiopia. A hospital-based cross-sectional study was conducted to collect primary data from 421 COVID-19 patients in Addis Ababa between May and July 2021. Logistic regression was used to identify factors associated with prehospital service utilization. Andersen's Behavioral Model was implemented to address independent variables, including predisposing, enabling, need, and health behaviors-related variables. The level of prehospital care utilization was 87.6%. Being married [AOR 2.6(95%; CI:1.24-5.58)], belief that self-transport is quicker than the ambulance [AOR 0.13(95%; CI: 0.05-0.34)], and perceptions that ambulance provides transportation service only [AOR 0.14(95%; CI:0.04-0.45)] were predisposing factors associated with prehospital service utilization while the source of referrals [AOR 6.9(95%; CI: 2.78-17.30)], and prior knowledge on the availability of toll-free ambulance calling numbers [AOR 0.14(95%; CI: 0.04-0.45)] were identified as enabling factors. Substantial proportions of critically ill COVID-19 patients used prehospital services to access treatment centers. Prehospital EMS utilization in this study varies by predisposing and enabling factors, particularly: marital status, source of referral, prior knowledge on the availability of toll-free ambulances, belief that self-transport is quicker than ambulances, and perceptions that ambulance provides transportation service only. Our findings call for further actions to be taken by policymakers including physical and media campaigns focusing on the identified factors.